Endometrial cells on Pap tests: ideal reporting is more complex than just finding the right age. Issue 7 (19th April 2017) - Fischer, Gabor; Haddad, Maha; Cormier, Karen
Abstract: Background: The age for reporting normal endometrial cells (EMCs) on Pap tests was changed to ≥ 45 years in the latest Bethesda update (2014). This recommendation is solely based on age with no consensus on optimal reporting guidelines. Methods: Pap tests with EMCs for women ≥40 years were retrieved from our Laboratory Information System (LIS). Patient age, last menstrual period (LMP) and available follow‐up histology were recorded. Follow‐up diagnoses were categorized as: no significant pathology, benign, hyperplasia ± atypia, or malignant. The Fisher's exact test was used to assess the association between categorical variables, p < .05 (two‐sided test) was considered significant. Results: Of the 352 cases with EMCs, 155 had surgical follow‐up. They showed no malignancy in the 89 women between 40‐49 years, compared with five malignancies in the 66 women 50+ years ( p = .016). The number of cases with significant pathology (hyperplasia and malignant) was 4 (40‐49 years) vs. 11 (50+ years) ( p = 0.029). The LMP was inconsistently provided (57%) and women identified as postmenopausal on requisition comprised all the malignancies and half the hyperplasias. Conclusion: Combined effort by pathologists and clinicians necessitates determining the best standardized clinicopathologic guidelines to report EMCs and appropriate follow‐up. Increasing the required age to ≥50 years would provide more optimal patient management; however, there are other considerations beyond age. Reporting EMCs in postmenopausal women is a reasonable alternative requiring consistent and accurate recording of LMP. Improving provided information for pathologists, determining reporting requirements for EMCs and standardizing clinical follow‐up should be a multidisciplinary effort. Diagn. Cytopathol. 2017;45:587–591. © 2017 Wiley Periodicals, Inc.